The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/femsec/fiw140
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of carbon loss and its temperature sensitivity in East-European subarctic tundra soils

Abstract: Arctic peatlands store large stocks of organic carbon which are vulnerable to the climate change but their fate is uncertain. There is increasing evidence that a part of it will be lost as a result of faster microbial mineralization. We studied the vulnerability of 3500-5900 years old bare peat uplifted from permafrost layers by cryogenic processes to the surface of an arctic peat plateau. We aimed to find biotic and abiotic drivers of CLOSS from old peat and compare them with those of adjacent, young vegetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 85 publications
2
10
0
Order By: Relevance
“…Second, the cumulative CO 2 fluxes in the wet mesocosms were partly determined by short‐term emission peaks, associated with a temporarily lowered water table during the thawing process (Figure S3a) and associated changes in peat redox chemistry caused by these water table fluctuations. These emission peaks show a reoxygenation of electron acceptors (Knorr & Blodau, ), but also indicate the presence of a labile C pool and active microbial community, well adapted to anaerobic conditions, as has been shown earlier for old peat soils (Diáková et al, ). Hence, the timing and magnitude of CO 2 emissions from wet mesocosms was governed by the position of the water table which, when lowered, enabled rapid out‐diffusion of CO 2 .…”
Section: Discussionsupporting
confidence: 53%
“…Second, the cumulative CO 2 fluxes in the wet mesocosms were partly determined by short‐term emission peaks, associated with a temporarily lowered water table during the thawing process (Figure S3a) and associated changes in peat redox chemistry caused by these water table fluctuations. These emission peaks show a reoxygenation of electron acceptors (Knorr & Blodau, ), but also indicate the presence of a labile C pool and active microbial community, well adapted to anaerobic conditions, as has been shown earlier for old peat soils (Diáková et al, ). Hence, the timing and magnitude of CO 2 emissions from wet mesocosms was governed by the position of the water table which, when lowered, enabled rapid out‐diffusion of CO 2 .…”
Section: Discussionsupporting
confidence: 53%
“…Thus, in terms of C pool parameters, the potential C release from the northern permafrost region will depend not only on SOC quantity but also on soil organic matter (SOM) lability (i.e., the rate at which soil organic matter will decay following warming and thawing). Laboratory incubation experiments that consider both different types of substrates (e.g., Schädel et al, 2014) and time of incubation (e.g., Elberling et al, 2013) are an important tool to assess potential C release from permafrost soils and deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Diakova et al (2016) also observed that certain microbial groups are capable of adjusting to the absence of oxygen and thriving under anaerobic conditions. Therefore, The soil carbon (C) and nitrogen (N) contents are measured by an elemental analyzer (vario Macro cube, Elementar, Germany).…”
Section: Aeration Statusmentioning
confidence: 95%
“…Q 10 evaluation is usually based on instantaneous CO 2 flux rates (Chang et al, 2012;Fang and Moncrieff, 2001;Karhu et al, 2014;Sun et al, 2016;Waldrop et al, 2010), time spans needed for an identical amount of C mineralization (Bracho et al, 2016;Wang et al, 2013;Zhu and Cheng, 2011), cumulative C flux over a given time period (Conant et al, 2008;Hamdi et al, 2013;Podrebarac et al, 2016), or microbial activity as a function of temperature (Diakova et al, 2016;Karhu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation